Nav1.5 cardiac sodium channels, regulation and clinical implications (2014)
Voltage-gated sodium channels constitute a group of membrane proteins widely distributed thought the body. In the heart, there are at least six different isoforms, being the Nav1.5 the most abundant. The channel is composed of an α subunit that is formed by four domains of six segments each, and four much smaller β subunits that provide stability and integrate other channels into the α subunit. The function of the Nav1.5 channel is modulated by intracellular cytoskeleton proteins, extracellular proteins, calcium concentration, free radicals, and medications, among other things. The study of the channel and its alterations has grown thanks to its association with pathogenic conditions such as Long QT syndrome, Brugada syndrome, atrial fibrillation, arrhythmogenic ventricular dysplasia and complications during ischemic processes.